Security Issuance and Stock Price Effects with Heterogeneous Beliefs - Weining, Niu; Shancun, Liu; Jing, Jin (Asian Economic and Financial Review, 2014)
We analyze the factors that affect security issuance and its impacts on the volatility of stock returns before and after the issuance under heterogeneous beliefs and short sale constraints using the issuing sample of convertible bonds, corporate bonds and stocks in China’s security market during 2007 to 2012. The empirical tests identify that abnormal turnover can portray heterogeneous beliefs much better than dispersion in analysts’ earnings forecasts. Firms’ pecking order of external financing is convertible bonds, stocks and corporate bonds for the bigger firm size and higher market to book ratio. However, for those firms with higher leverage, issue amount and market volume, their optimal options are stocks, convertible bonds and then corporate bonds. The empirical results also reveal that convertible bonds issuance has a negative impact on price-earnings, but this effect diminishes in the long run. Besides, the influence of stock issuance on its return is negative only on the seasoned equity offering day. However, there is no significant effect on the yield rate in a short-term if corporate bonds are issued. Heterogeneous beliefs have a significant impact on the stock return, while negative for convertible bonds and positive for stocks and corporate bonds.